Coexistent sarcoidosis and lymphangioleiomyomatosis in a patient with cystic lung disease. Issue 2 (28th November 2018) - Cullivan, Sarah; De La Harpe Golden, Peter; Doyle, Deirdre; Doddakula, Kishore Kumar; Burke, Louise; Murphy, Desmond Michael
Abstract : A 45‐year‐old lady presented acutely with pleuritic chest pain, haemoptysis, and dyspnoea. Her background was significant for a 1.4 cm renal angiomyolipoma, and she was an ex‐smoker without any relevant family history. A computed tomography (CT) pulmonary angiogram was negative for a pulmonary embolism but demonstrated diffuse cystic change throughout both lungs. A bronchoscopy confirmed a normal endobronchial tree, and pulmonary function tests demonstrated moderate airways obstruction, with reversibility and a normal diffusion capacity for carbon monoxide (DLCO). A video‐assisted thoracoscopic surgery (VATS) lung biopsy showed non‐caseating granulomas, and serum angiotensin converting enzyme (ACE) was elevated consistent with a diagnosis of pulmonary sarcoidosis. Further sectioning indicated focal areas that stained positive for Human Melanoma Black 45 (HMB‐45), confirming lymphangioleiomyomatosis (LAM). A diagnosis of cystic lung disease secondary to coexistent sarcoidosis and LAM was made. Abstract : This is an interesting case of coexistent lymphangioleiomyomatosis and pulmonary sarcoidosis in a 45‐year‐old lady with cystic lung disease. This case highlights important clinical, radiological, and physiological features of both conditions and suggests a potential shared disease mechanism.